Architecture of buried reverse fault zone in the sedimentary basin: A case study from the Hong-Che Fault Zone of the Junggar Basin. (December 2017) - Liu, Yin; Wu, Kongyou; Wang, Xi; Liu, Bo; Guo, Jianxun; Du, Yannan
Abstract: It is widely accepted that the faults can act as the conduits or the barrier for oil and gas migration. Years of studies suggested that the internal architecture of a fault zone is complicated and composed of distinct components with different physical features, which can highly influence the migration of oil and gas along the fault. The field observation is the most useful methods of observing the fault zone architecture, however, in the petroleum exploration, what should be concerned is the buried faults in the sedimentary basin. Meanwhile, most of the studies put more attention on the strike-slip or normal faults, but the architecture of the reverse faults attracts less attention. In order to solve these questions, the Hong-Che Fault Zone in the northwest margin of the Junggar Basin, Xinjiang Province, is chosen for an example. Combining with the seismic data, well logs and drill core data, we put forward a comprehensive method to recognize the internal architectures of buried faults. High-precision seismic data reflect that the fault zone shows up as a disturbed seismic reflection belt. Four types of well logs, which are sensitive to the fractures, and a comprehensive discriminated parameter, named fault zone index are used in identifying the fault zone architecture. Drill core provides a direct way to identify different components of the fault zone, the fault core is composed of breccia, gouge, and serpentinized or foliated fault rocks and the damage zone develops multiphase of fractures, which are usually cemented. Based on the recognition results, we found that there is an obvious positive relationship between the width of the fault zone and the displacement, and the power-law relationship also exists between the width of the fault core and damage zone. The width of the damage zone in the hanging wall is not apparently larger than that in the footwall in the reverse fault, showing different characteristics with the normal fault. This study provides a comprehensive method in identifying the architecture of buried faults in the sedimentary basin and would be helpful in evaluating the fault sealing behavior. Highlights: A new method is set up in identifying the architecture of buried reverse fault. A power-law relationship exists between the width of fault core and damage zone. Recognition of fault zone architecture helps to evaluate the fault seal capacity.